Challenges Associated with formalising Artisanal Small-Scale Mining in Ghana - Rejoice Selorm Wireko-Gyebi; Imoro Braimah; David Anaafo; Abdul-Wadood Moomen; Anne Mette Lykke (SAGE Open)
The illegal artisanal and small-scale mining (ASM) activities in Ghana are persistently booming even after governments’ several attempts to halt the menace and streamline their modus operandi towards formalisation. This is because the formalisation attempts by the governments of Ghana have been associated with several challenges. Hence, this paper examines the challenges hampering the formalisation of illegal ASM in Ghana and the ways to overcome these challenges. The cross-sectional survey research design and the mixed methods approach were adopted to understand miners’ experiences and challenges with formalisation in Ghana. The study uses three mining districts (Wassa Amenfi East Municipality, Amansie West, and Talensi Districts), where there is the proliferation of illegal ASM activities, as case study areas. The findings reveal that the formalisation initiatives by governments fail to capture: (1) the cause-effect relationships that drive illegal ASM, and (2) the interest and objectives of the illegal ASM operators. The cause-effects include observed complex, cumbersome, and expensive license acquisition procedure, red-tapesim, corruption, and disregard for customary laws. This paper, therefore, concludes that to ensure effective formalisation, there must be a free and fair regular public and stakeholder engagement, an established feedback mechanism among stakeholders, and ASM operator-centred approaches to formalisation. The paper further proposes the decoupling of ASM from the Minerals Commission and the Ghana Chamber of Mines and a consequent establishment of a Commission for ASM and Chamber of ASM.